SIFAT PAPAN WOL KAYU DARI 12 JENIS KAYU HUTAN TANAMAN INDUSTRI - I M Sulastiningsih; Rozak Memed; Paribotro Sutigno (Jurnal Penelitian Hasil Hutan, 1988)
The results  of  laboratory  test  of  wood-wood board properties  made from  12 individual  wood species obtained  from West Java, Lampung  and East Nusa Tenggara province are reported  in this paper.  The properties tested  were board density, moisture  content,   thickness  reduction   due  to compression  and bending strength.The study  has revealed  that  Eucalyptus  urophylla  and  Eucalyptus platiphylla F.V.M.  obtained  from  natural forests are impossible  to plane  because  they  are very  hard.  The average yield  of  wood-wool   from  the  rest is 454.43 kg percubic meter  of  log input. These  wood-wool   can  be processed   to  become wood-wool boards without first  immersing  them  in cold  water.   The physical  and  mechanical  properties   of  wood-wool   boards made  from  seven  wood species  (meranti  merah I, pinus  I,  mahoni  uganda,  meranti  tembaga,  leda,  akasia and  meranti  merah II) catalyzed  with  CaCl2 solution  are in conformity with  the DIN 1101Standard.   However, only  four  wood  species  (meranti  merah  I,  meranti  tembaga, leda and meranti  merah II)  catalyzed with  Ca(OH)2 suspention meet  the standard  requirement.